Effects of afforestation with different species on carbon pools and soil and forest floor properties - Guner, Sukru Teoman; Erkan, Neşat; Karatas, Riza (Elsevier, 2021)
Land use and land use change are factors that affect carbon and nutrient stocks in ecosystems. The aim of this research was to determine the effects of forest land use types on carbon pools and soil and forest floor features. This study was conducted in areas afforested with black pine (Pinus nigra Am. subsp. pallasiana Lamb. Holmboe) and Scots pine (Pinus sylvestris L.) and on adjacent bare land within the Akdag Nature Park, which is located in the West-Central Anatolia Region of Turkey. Three 20 x 20 m sample plots were selected within each forest land use, and the diameters at breast height and heights of all trees were measured. Tree biomass and carbon stocks in the unit areas were calculated using tree biomass equations, and carbon conversion factors were developed for two tree species. Within each sample plot, disturbed and core soil samples and forest floor samples were taken at three points at depths of 0-10, 10-20 and 20-30 cm. The physical and chemical properties of the soil and forest floor samples were determined in the laboratory and measurements were converted to a unit area using volume values. The data were evaluated using independent sample t-tests and analysis of variance. The results showed that the ecosystem carbon (C) stocks differed significantly with forest land use type; black pine plantations, Scots pine plantations and bare land accumulated 235.2 t C ha(-1), 206.1 t C ha(-1) and 37.4 t C ha(-1), respectively. We found that in addition to the positive effect of afforestation on soil, black pine had a greater impact on some forest floor and soil characteristics in the region than Scots pine. Thus, we suggest that priority should be given to black pine in afforestation of the region and in other ecosystems with similar climates. Additionally, our results reveal the importance of afforestation on bare lands for reducing the impact of global climate change.
Erkan, Nesat/0000-0003-1800-4926
Keywords: Land-use change; Pinus nigra; Pinus sylvestris; Ecosystem; Carbon pools; Nutrient stocks